Developing an assessment instrument of junior high school students’ higher order thinking skills in mathematics - Samritin Samritin; Suryanto Suryanto (REID (Research and Evaluation in Education), 2016)
This study is a research and development study. It aims to produce an instrument for assessing junior high school (JHS) students’ higher order thinking skills (HOTS) in mathematics. Its procedure consists of nine steps: (1) Constructing the test specification; (2) writing test items; (3) analyzing test items; (4) conducting the first tryout; (5) analyzing the results of the first try out; (6) revising the test; (7) assembling the test; (8) conducting the second tryout; and (9) analyzing the results of the second tryout. The instrument content validity was obtained through the focus group discussion (FGD) forum, and Delphi technique. The construct validity was found out through the tryout data analysis. The instrument tryout was conducted twice involving 264 participants in the first tryout and 821 participants in the second tryout. The results of the study indicate that the instrument for assessing JHS students’ HOTS in mathematics has met the validity and reliability criteria. From the results of the content validity analysis, it can be concluded that the instrument is valid, and it was supported by the items validity indices above  0.79. From the results of the construct validity analysis, it can be concluded that the instrument is valid, as indicated by the value of χ2 = 67.69, with p-value = 0.10, Root Mean Square Error of Approximation (RMSEA) = 0.03, supported by Goodness of Fit Index (GFI) of 0.97, Normed Fit Index (NFI) of 0.95, and Adjusted Goodness of Fit Index (AGFI) of 0.95. The instrument reliability is 0.88. The developed instrument for assessing HOTS in mathematics consists of 12 items, each of which is of essay test type. The test items have difficulty indices in a range of 0.30 ≤ Pi ≤ 0.7.